"REFUGEE LOVE" IN A COLLEGE ART GALLERY: "Refugee Crafts" in the American Political Imaginary, 2017. (19th November 2021) - Rodgers, Susan
Abstract : Refugees are often mischaracterized as either "threats" to their new nations of resettlement or as remarkably virtuous, resilient "survivors" of harsh expulsions from their home countries and difficult years in refugee camps. Both imageries fall short of forced migrants' actual lives and stories. Museums' display practices and their interpretations of "refugee arts" can easily fall into stereotypes, especially sugary, positive ones. This case study delves into display practices that led well‐intentioned curators and their student collaborators to lodge a small exhibition's vision of refugees and their art production at superficial levels. Many universities now encourage students to conduct community‐based research and display findings in campus museums. This study argues that even well‐motivated shows on forced migrants' art production should be executed with subtlety, so as to avoid inaccurate classification schemes regarding "refugee art."